2014
DOI: 10.2146/ajhp130318
|View full text |Cite
|
Sign up to set email alerts
|

Designing a resident research program

Abstract: Development of an RRAB increased residents' manuscript publication and poster presentation rates and facilitated the research process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Pharmacists who completed research programs during residency, regardless of publication success, report using the research skills learned during the program, felt comfortable serving as a PGY1 research project mentor, and actively pursued research after residency. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists who completed research programs during residency, regardless of publication success, report using the research skills learned during the program, felt comfortable serving as a PGY1 research project mentor, and actively pursued research after residency. 32 …”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Pharmacy residents completing a mentored research program that covers topics such as research plan development, data analysis and manuscript development are more likely to publish their project. [21][22][23][24][25] These programs should incorporate both didactic and experiential pedagogical strategies.…”
Section: A J P Ementioning
confidence: 99%
“…11 Our findings complement those of other researchers, who have reported increased success securing publication of pharmacy resident research projects after the implementation of research training programs. 16,28 Similar improvements have been reported in other health professions, for example among medical residents; Basu et al 29 described a program called CARE (Consolidated Academic and Research Exposition) that instructed internal medicine residents in basic research skills and subsequently increased residents' scholarly activity by 110%. Ogunyemi et al 30 reported that a structured, faculty-mentored research program within a medical specialty training program for obstetrics and gynecology residents increased the rate of publication in the peer-reviewed literature by 180%.…”
Section: Discussionmentioning
confidence: 65%